Preparation and Optimization Formula of Whey Protein-Pectin Complex As Nanocapsules for Lemon (Citrus limon) Juice - Lailatul Azkiyah; Yukihiro Yamamoto; Shinjiro Ogita; Tomoyuki Yoshino (International Journal on Food, Agriculture and Natural Resources, 2020)
Lemon (Citrus limon) juice was nanoencapsulated in whey protein concentrate (WPC)-pectin complex coacervates, and then dried using freeze-drying to produce solid nanocapsules. To optimize the nanoencapsulation condition, central composite design (CCD) of response surface methodology (RSM) was implemented. WPC (%), pectin (%) and pH level were taken as variables, while antioxidant activity and D-limonene content as responses. The optimized condition was in 6.0% WPC and 3.0% pectin at pH 3.1 by maximize the responses. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) images showed the morphology of lemon juice nanocapsules as spherical nanoparticles with an average size of 22.3 nm.